Nilai-Nilai Pendidikan Tata Busana dan Rias Srimpi Pandhelori dalam Perspektif Hermeneutik - Wenti Nuryani; Suminto A Sayuti; Dwi Siswoyo (LP2M ISBI Bandung, 2020)
ABSTRACTThis research was a descriptive qualitative research using a hermeneutic approach and was aimed atrevealing the meaning of traditional symbols contained in Yogyakarta-style Srimpi Pandhelori dancecostumes and makeup. The symbols in Srimpi Pandhelori costumes and makeup are the media thattransform noble characters. It is closely related to the character building based on local genious. Therefore,this research is aimed at describing the symbols found in Srimpi Pandhelori dance as an absorptionelement of the noble character values. Every instrument in costumes and makeup represents local wisdomwhich is designed to be a medium of noble character education. The main data collection technique ofthe research was direct observation of Srimpi dance performances strengthened by records. The datawere validated by using credibility techniques by doing 1). observation perseverance, 2). triangulationof methods and sources, 3). peer discussion, and 4). adequacy of references. The data analysis used inthis research was a dialectical hermeneutics approach i.e. the approach where interpretation proceduresto obtain meaning uses elements of analysis from Madisson called a normative method consisting ofcoherence, comprehensiveness, contextuality, penetration, and appropriateness. The results show thateach instrument in costumes and make up of Srimpi Pandhelori dance pattern contains symbols. Thesesymbols contain educational values, namely: the value of self-control education, the value of educationabout accuracy, the value of Godhead education.Keywords: values, Srimpi Pandhelori, hermeneuticABSTRAKPenelitian ini merupakan penelitian deskriptif kualitatif dengan menggunakan pendekatanhermeneutik, bertujuan untuk mencari makna dari simbol-simbol tradisi dalam rias dan busanatari srimpi Pandhelori gaya Yogyakarta. Simbol-simbol dalam rias dan busana tari srimpi Pandhelorimerupakan media mentransformasikan budi pekerti luhur. Hal tersebut berkaitan erat denganpembagunan karakter yang didasarkan pada local genious. Oleh sebab itu dalam penelitian inimencoba menguraikan simbol-simbol dalam tari Srimpi Pandhelori sebagai unsur serapan nilainilaibudi pekerti luhur. Setiap insrumen dalam rias busana merupakan representasi kearifanlokal yang dimaksudkna menjadi media pendidikan budi pekerti luhur. Teknik pengumpulandata yang utama adalah pengamatan secara langsung pertunjukan tari Srimpi yang diperkuatdengan rekaman. Untuk keabsahan datanya menggunakan teknik kredibilitas yang dilakukandengan cara: 1). ketekunan pengamatan, 2). trianggulasi metode dan sumber, 3). diskusi sejawat,4). kecukupan referensi. Sementara analisis datanya menggunakan pendekatan hermeneutikadialektis, dimana prosedur penafsiran dalam rangka memperoleh makna menggunakan unsurunsuranalisis dari Madisson yang disebutnya sebagai metode normatif, terdiri dari coherence,comprehensiveness, contextuality, penetration, appropriateness. Hasil penelitian menunjukan setiapinstrumen dalam rias dan busana dalam tari Srimpi Pandhelori merupakan simbol. Dalamsimbol tersebut mengandung nilai-nilai pendidikan yaitu: nilai pendidikan pengendalian diri,nilai pendidikan tentang kecermatan, nilai pendidikan Ketuhanan.Kata Kunci: Nilai-Nilai Pendidikan, Srimpi Pandhelori, hermeneutik